Distributed refinement algorithm for WSN localization - Ying-biao YAO; Nan-lan JIANG (Tongxin xuebao)
A distributed refinement algorithm was proposed based on the error analyzing of range-based WSN localization.In each iteration,the proposed algorithm identified “error nodes” and “effective nodes” according to the idea of“magnetic pole”at first; then,it choosed two nodes with the minimum relative deviations in the 1-hop neighbors set of error node,and getted the intersection points of two circles whose centers were the positions of above two nodes and radiuses are the range distances from above two nodes to the error node respectively; at last,it choosed the position with minimum error,from its current position and above two intersection points as refinement position of error node after this iteration.Simulation results show that the proposed algorithm can reduce the localization error of multilateral positioning model and improve the localization accuracy efficiently.